Characterization of enzyme and encoding gene of thermostable peroxidase from Bacillus sp. PHS 155 - Sasithorn Thongma (Prince of Songkla University, 2020)
Thesis (M.Sc., Biotechnolgy)--Prince of Songkla University, 1997